TINJAUN YURIDIS PEMENUHAN HAK KEBUTUHAN SEKSUAL TERHADAP WARGA BINAAN YANG TELAH MEMILIKI STATUS PERKAWINAN DI LEMBAGA PEMASYARAKATAN - Amin, Mohamad Safiqul; Sutrisno, Bambang (MIZAN, Jurnal Ilmu Hukum, 2024)
This study examines the juridical review of fulfilling the rights of sexual needs for convicts who already have marital status in correctional institutions. inmates who already have marital status from the perspective of human rights. This research method uses normative legal research. The results of this study explain that in general the regulation of the rights of assisted citizens has been regulated in Law Number 22 of 2022 concerning Corrections and related provisions regarding the conditions and procedures for exercising the rights of assisted citizens have been regulated in Government Regulation of the Republic of Indonesia Number 32 1999 concerning Terms and Procedures for the Implementation of the Rights of Correctional Families. And until now the state has not regulated the right to fulfill the sexual needs of inmates who already have marital status so that it is believed to have a negative impact on the deviant sexual behavior of inmates. happy that the State should not prevent this, so that the non-fulfillment of the sexual needs of inmates who are bound by marriage becomes one of the violations of human rights committed by the State.